Health data collecting and sharing: case studies of Czech e-health applications - Zvárová, Jana; Lhotská, Lenka; Seidl, Libor; Zvára, Karel (Studies in health technology and informatics, 2012)
The paper shows the importance of e-health applications for electronic healthcare development. It describes several e-health applications for health data collecting and sharing that are running in the Czech Republic. These are IZIP system, electronic health record MUDR and K4CARE project applications. The e3-health concept is considered as a tool for judging e-health applications in different healthcare settings.
Keywords: šíření informací; Electronic Health Records; Medical Record Linkage; chorobopisy - spojování; Česká republika; ukládání a vyhledávání informací; Czech Republic; Information Dissemination; Information Storage and Retrieval; Case-Control Studies; zdravotní záznamy osobní; Health Records, Personal; elektronické zdravotní záznamy; studie případů a kontrol